Ultra-Reiz Current Appears to be More Effective Modality than Interferential for People with Knee Osteoarthritis: A Randomized Block Clinical Trial - Mahnaz Ahangari; Amin Norouzi Fashkhami; Hamid Zinalpoor; Hamed Ahangari; Mohamad Reza Minator Sajjadi (Universitas Udayana dan Diaspora Taipei Medical University, 2020)
Introduction: Today, increased degenerative disease of the knee, which reduces the efficiency of the activity and quality of life, is one of the most common causes of many population complaints. It is important to properly plan and carry out non-invasive and non-pharmacological therapies to treat the pain and its consequences. The question of which of methods effectively relieves pain, improve function and efficiently increases life quality led to a comparison of two methods, interferential and ultra-reiz (Träbert) currents therapy. Methods: Randomized Block clinical trial carried out at Taleghani general hospital Shahid Beheshti University of Medical Sciences from November 2017 to February 2019. The study included 104 patients of both sexes, aged 38-74 years, with knee osteoarthritis. They were selected based on exclusion and inclusion criteria. The patients were randomly assigned to two groups: A and B. Group A, n: 52 patients, were received ultra-reiz current, and group B, n: 52 patients, were subjected to interferential current. Parameters assessment were evaluated by the Knee Injury and Osteoarthritis Outcome Score (KOOS) questionnaire with 5 domains: pain, symptoms, ADL, sports/recreational activity, and quality of life. Data were collected at the 1st session and at the end of treatment (at least three times a week). The obtained results were subject to statistical analysis. Results: Data were analyzed in SPSS software by using paired and two independent sample t-test. The mean scores before and after treatment with p-value range 0.002 0.764 showed that there were differences in pain, other symptoms, ADL, sport/recreational activity, and quality of life status between ultra-reiz and IFT groups, but the results were statistically more significant in the ultra-reiz group (p < 0.0001). Conclusions: Our study showed that ultra-reiz and IFT were effective for patients with knee OA, but ultra-reiz became a more effective modality than IFT in OA patients.